The Development of Teaching Materials for Science of Nahwu Muyassar by Syauqi Dhoif Using a Constructivist Approach for Beginners at Islamic Boarding School - Mustofa, Nurul Hana; Hasanah, Mamluatul; Huda, Miftahul (Arabiyatuna: Jurnal Bahasa Arab, 2024)
This research aimed to 1) explain the process of preparing the Simplified Grammar Book by Shauqi Dhoif in light of the constructivist theory is for beginners, and 2) determine the effectiveness of the developed Simplified Grammar Book. The development of Nahwu teaching materials was initiated due to several backgrounds, including: The unavailability of Nahwu teaching materials in Islamic boarding schools focusing on practical aspects, lack of supporting teaching materials for students to understand Nahwu, and the emphasis on the importance of improving Arabic text reading skills among students. These issues were addressed through this research. The researchers in this study used Research and Development (R&D) methodology, following nine steps out of the ten proposed by Borg and Gall. These entailed needs analysis, data collection, product design, product validation, improvement of the first product, individual product testing, improvement of the second product, field testing of the product, and improvement of the final product. The results of this research are as follows: 1) The developed educational materials consisted of 25 units to be implemented in 8 sessions. The educational materials included various exercises in grammar enhancing the understanding of grammar and analyzing Arabic linguistic texts. 2) The effectiveness of using the educational materials became evidence through the analysis of expert questionnaire data, which received a score of 86.5, classified as "good." The student questionnaire results also scored 86.6, categorized as "good." While the pre-test score was 57.0000, after using the developed teaching materials, the students scored 75.6800. This indicated a significant increase and the book was very effective for improving students' grammar knowledge and skills. The theoretical contribution of this research is that grammar teaching materials based on constructivist theory using the Shauqi approach can contribute to enhancing students' ability to understand and analyze Arabic texts.